Early recognition of dementia within the family - Zsarnóczky, Martin; Zsarnóczky-Dulházi, Fanni (Magyar Gerontológia, 2020)
The awareness of communities with dementia in Western Europe has moved closer to recognizing priority issues such as the environment or climate change. Dementia-friendly communities how have a history of 30 years and have achieved significant results through their work, both for those affected by the disease and those not directly affected. It probably affects many families, the topic is also getting into the spotlight in Hungary.Without specific and detailed statistics and databases, dementia currently exists in the latent zone. The vast majority of the literature defines dementia as a diesease for which there is no treatment or cure. The effect of dementia is considered primarily as problems in the brain that negatively affect clear thinking, memory processes and result in additional emotional turbulence. Dementia is known as an age-related condition.In general, dementia is identified as senility, incorrectly. Dementia can occur in different areas and at different levels in individual patients. As a result, families affected by the disease often face serious difficulties in identifying the disease. Without proper and detailed knowledge of the diagnosis, many families struggle with the situation of self care solutions at home. This personal involvement not only imposes a significant financial and emotional burden on the family but also often leads to separation and isolation, which can have additional negative effects on the disease itself and even on the mental health of the patient’s family members.The global extent of dementia is generally known only to experts in the field, and to this day there is still a lack of adequate representation in the wider social dialogue. There is a unique and innovative incentive in Gyöngyös where Matralab’s integrated care centers offer day-care activities and solutions to support and provide experts advice to families with dementia. The project is implemented at the regional level, where 25 municipalities start monitoring the conditions and impacts of dementia in the region. As dementia is a prevalent and identifiable condition, affected families need help and support at the widest possible level.